2001
DOI: 10.1007/s005340170055
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ruptured undifferentiated sarcoma of the liver in children: a report of two cases and review of the literature

Abstract: Undifferentiated (embryonal) sarcoma of the liver (USL) is a highly malignant tumor of early life. Treatment choices for USL, especially with intraperitoneal rupture, are uncertain. Outcomes have been almost uniformly poor until recently. We describe two 7-year-old girls treated for ruptured USL. In the more recent patient, operative biopsy was followed by three cycles of cisplatin (CDDP), adriamycin (ADR), and cyclophosphamide (CPM). A fluid-filled cavity in the tumor showed enlargement and was drained. Two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 17 publications
1
24
0
1
Order By: Relevance
“…There are more data on the treatment of patients with sarcoma protocols [7,8,13,14,26,27] than those with hepatoblastoma protocols. [17][18][19]30,31] Such reports do not lend themselves to rigorous statistical analysis, but the relatively high survival rate in patients treated on sarcoma protocols implies acceptable efficacy. Since the camptothecin analogues irinotecan and topotecan are promising new agents in treating rhabdomyosarcoma, they may prove to be of use in treating UESL.…”
Section: Discussionmentioning
confidence: 99%
“…There are more data on the treatment of patients with sarcoma protocols [7,8,13,14,26,27] than those with hepatoblastoma protocols. [17][18][19]30,31] Such reports do not lend themselves to rigorous statistical analysis, but the relatively high survival rate in patients treated on sarcoma protocols implies acceptable efficacy. Since the camptothecin analogues irinotecan and topotecan are promising new agents in treating rhabdomyosarcoma, they may prove to be of use in treating UESL.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of chemotherapy for treating PLS in the literature are controversial, and a variety of chemotherapeutic regimens were used in these case reports, including doxorubicin, ifosfamide, vincristine, actinomycin-D, cyclophosphamide (VAC), cisplatinum, carboplatinum, ifosfamide, and etoposide. European hospitals prefer VAC regimen or chemotherapy with a modified VAC backbone, but in China, we tend to use chemotherapy regimen (vincristin, cisplatin, cyclophosphamide and adriamycin) [24-29]. Merli et al [27] treated 13 undifferentiated liver sarcoma patients with surgery and postoperative chemotherapy according to the European protocol (7 patients with neoadjuvant chemotherapy).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [28] reported that an undifferentiated embryonal sarcoma of the liver patient who underwent interventional therapy and surgical resection exhibited a prolonged survival compared with patients who underwent surgical resection only. Uchiyama et al [29] proposed that surgical resection combined with chemotherapy is the most effective therapy for undifferentiated embryonal sarcoma of the liver patients with tumor rupture. Recently, Noguchi et al [30] reported a long-term survival case of USEL who was treated with a high dose of etoposide and radiation therapy, then followed with peripheral blood stem cell trans-plantation.…”
Section: Discussionmentioning
confidence: 99%
“…O sarcoma embrionário é considerado uma neoplasia agressiva e de prognóstico desfavorável, com sobrevida de 1 a 2 anos. Nos casos em que há predomínio de padrão cístico, a ruptura da neoplasia é uma complicação importante (7,22) . Nas últimas décadas, o prognóstico dos pacientes com sarcoma indiferenciado do fígado melhorou expressivamente, com a associação da ressecção cirúrgica completa do tumor e tratamentos adjuvantes, principalmente novos protocolos quimioterápicos (2,23,24) .…”
Section: Discussionunclassified